2018
DOI: 10.1111/1365-2745.12924
|View full text |Cite
|
Sign up to set email alerts
|

Ecosystem nitrogen retention is regulated by plant community trait interactions with nutrient status in an alpine meadow

Abstract: Biotic nitrogen (N) retention is an important ecosystem function in the context of ongoing land‐use intensification, N deposition and global warming. However, a paucity of experimental evidence limits understanding of how different plant community components influence N retention in terrestrial ecosystems. In this investigation, we conducted a 15N labelling experiment to test how plant community properties, including plant species richness/diversity, dominance and functional traits, influence plant N uptake an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
16
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 78 publications
4
16
1
Order By: Relevance
“…When analyzing the influence of environmental factors on the fungal community, it was found that nitrogen (nitrate, ammonium and total nitrogen) was the most important environmental factor affecting the fungal community in alpine lakeside wetlands. A large number of reports show that the diversity of nitrogen uptake patterns of plants in the Qinghai-Tibet Plateau is relatively high, thereby enriching plant diversity in the plateau [51,52]. Plants are an essential source of nutrients for soil fungal communities, and fungal communities are closely related to plant communities [53][54][55].…”
Section: Discussionmentioning
confidence: 99%
“…When analyzing the influence of environmental factors on the fungal community, it was found that nitrogen (nitrate, ammonium and total nitrogen) was the most important environmental factor affecting the fungal community in alpine lakeside wetlands. A large number of reports show that the diversity of nitrogen uptake patterns of plants in the Qinghai-Tibet Plateau is relatively high, thereby enriching plant diversity in the plateau [51,52]. Plants are an essential source of nutrients for soil fungal communities, and fungal communities are closely related to plant communities [53][54][55].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, our findings from the late growing season may not reflect ecosystem N uptake and retention in the early growing season. The average total amount of 15 N retained in our systems was relatively high (73%) compared to N retention in temperate grasslands (Wang et al, 2018, De Vries, Bloem, et al, 2012, Templer et al, 2012, and comparable to shrubland N retention (Templer et al, 2012). However, it is important to note that we only collected intact soil cores that included plants, whereas plant cover was sparse during early successional stages.…”
Section: Accepted Articlementioning
confidence: 91%
“…Soil acidity derived directly or indirectly from N deposition ( Liu et al, 2012 ; Greaver et al, 2016 ) can lead to migration of metals, a loss of basic cations, an imbalance among N-containing compounds, and the ultimate alteration of THE composition of a plant community ( Stevens et al, 2010 ; Laliberté et al, 2014 ). N is generally known to be the limiting factor in most terrestrial ecosystems ( Jing et al, 2016 ; Wang et al, 2018 ). Some scholars believe that an increasing N deposition rate may lead to the transition from N limitation to N saturation in ecosystems ( Lu et al, 2010 ), which may benefit the coexistence of species by excluding non-nitrophilous plants ( Bobbink et al, 2010 ).…”
Section: Introductionmentioning
confidence: 99%
“…N deposition can positively affect the functional groups of grass by promoting their growth and negatively impacting other functional groups, such as forbs by limiting their growth ( Johansson et al, 2012 ; Borer et al, 2014 ; Humbert et al, 2016 ; Zhang et al, 2020 ). Until present, the limited studies from temperate and tropical forests have shown inconsistent results about the responses of the functional traits of plants to N deposition, i.e., some scholars stated that functional traits were the conductors of the N deposition on communities ( Wang et al, 2018 ), whereas some other scholars reported that plant traits were not related to N deposition ( Moreau et al, 2015 ). In addition, it is even less clear about the responses of functional traits of plants from dominant species to functional groups, and whole communities in different types of grassland to N deposition were consistent with the same or different.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation